KONSEP KEPEMIMPINAN KRAMAN TELU LIKUR SEBAGAI MODEL PENDIDIKAN AGAMA HINDU DI DESA ADAT SUKAWANA KECAMATAN KINTAMANI KABUPATEN BANGLI - Kadek Ediyana (JAPAM (Jurnal Pendidikan Agama), 2025)
The Sukawana traditional village in Kintamani sub district, Bangli Regency, Bali Province, which still adheres to its traditional government system based on the Ulu Apad system. In running the wheels of its traditional government, it is known as Kraman Telu Likur, whose highest leader is Jero Kubayan Kiwa Tengen. The concept of Kraman Telu Likur in the Hindu religious education model in the Sukawana Traditional Village can be seen through the organizational structure of Kraman Telu Likur. Kraman Telu Likur is a traditional leadership organization based on ulu apad which is thick with the culture of ancient Balinese village leadership. The leadership within Kraman Telu Likur not only provides management of traditional life, but also practices educational functions such as providing motivation to residents regarding the consistency of ancient traditions and becoming a facilitator in the education efforts of ancient Sukawana traditions. The educational values that can be learned from the Kraman Telu Likur Hindu religious education model are the values of Hindu leadership education and local wisdom education. The educational model applied by KramanTelu Likur in carrying out education and leadership in the Sukawana Traditional Village consists of a participation-based education model that is apparent through the openness of Kraman Telu Likurin accepting every cognitive discussion about Ancient Bali. The impact of Kraman Telu Likur on theyounger generation in Sukawana Traditional Village is to improve character and spirituality as a result of obedience to the ideology held by Kraman Telu Likur in terms of directing its younger generation to make religious traditions a path of devotion and karma marga. The strength of character and spirituality possessed by the younger generation of Sukawana strengthens the regeneration of the formation of prospective Kraman Telu Likur administrators who will later obey the dresta of Ancient Bali and the local Hindu leadership system typical of Sukawana. All of them areinvolved as part of the preservation of local traditions and culture as admired by the public in Sukawana Traditional Village.